Peran Komunikasi Antarbudaya dalam Membangun Toleransi di Desa Kepaon Denpasar Bali (Studi Kasus Takbiran Keliling) - Rosalia, Leny; Saleh, Muhamad; Fakhri, Mohammad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the role of intercultural communication in fostering religious tolerance during the implementation of the takbiran keliling tradition in Kepaon Village, South Denpasar, Bali. Kepaon is a multicultural area inhabited by a Hindu majority and a significant Muslim minority, both of whom have maintained harmonious relations through effective communication and strong cultural acculturation. This research employs a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. Informants include Hindu customary leaders, Muslim religious figures, banjar leaders, pecalang, takbiran organizers, youth groups, and local residents involved in the event. The findings reveal that intercultural communication in Kepaon is effective due to intensive coordination among religious leaders, the use of local languages and cultural symbols, and continuous social interaction between Hindus and Muslims. The takbiran keliling, which often contains the potential for conflict in other regions, becomes a space for collaboration and active tolerance in Kepaon, supported by Hindu communities, pecalang escorts, and beleganjur performances by Hindu youth. This study concludes that intercultural communication based on local wisdom such as Menyama Braya and long-standing genealogical ties is crucial in maintaining social harmony. The results provide valuable insight into intercultural communication practices in multicultural settings and offer a model for managing minority religious activities peacefully in other regions.